1990
DOI: 10.1111/j.1651-2227.1990.tb11553.x
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Neonatal Serum Thyroglobulin Determinations in the Follow‐up of Patients with Congenital Hypothyroidism

Abstract: Serum thyroglobulin was determined in 68 newborn infants with positive screening tests for congenital hypothyroidism. In 38 infants the diagnosis was confirmed (patients), but the remaining 30 were euthyroid at follow-up (controls). The mean thyroglobulin concentration at the age of 2 weeks did not differ significantly between the patients and the controls (179 vs. 125 micrograms/l). Thyroid scintigraphy was performed in 15 patients. All seven with thyroid aplasia, based on 99mTc pertechnetate scintigraphy, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…However, an important radioiodine uptake would have been observed on the thyroid scintigraphy [3-5]. Secondly, the mother’s hypothyroidism could have been caused by TBAbs, a hypothesis which is consistent with the absence of radioiodine uptake associated with a normal thyroid gland on ultrasound [4, 5] and a normal rate of thyroglobulin, although this thyroglobulin level may be considered low for a newborn with such a high TSH [4, 5, 17-19]. This second hypothesis is supported by the transitory nature of neonatal hypothyroidism in parallel with the decrease in TRAbs.…”
Section: Discussionmentioning
confidence: 99%
“…However, an important radioiodine uptake would have been observed on the thyroid scintigraphy [3-5]. Secondly, the mother’s hypothyroidism could have been caused by TBAbs, a hypothesis which is consistent with the absence of radioiodine uptake associated with a normal thyroid gland on ultrasound [4, 5] and a normal rate of thyroglobulin, although this thyroglobulin level may be considered low for a newborn with such a high TSH [4, 5, 17-19]. This second hypothesis is supported by the transitory nature of neonatal hypothyroidism in parallel with the decrease in TRAbs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that many patients with permanent CH have measurable Tg levels in serum [18][19][20][21][22][23]. These Tg values are believed to be due to secretion from residual thyroid tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of Tg measurement in the follow-up of CH children has never been established. Ilicki et al [18] concluded that serum Tg levels measured at the time of diagnosis are of limited value in forecasting psychomotor development. In this study we demonstrate that more than half (28/51) of our permanent CH children have measurable Tg levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an early study of congenital hypothyroidism, no significant differences in serum Tg were found between neonates with thyroid aplasia confirmed by thyroid scintigraphy (range ¼ 15-290 mg/L) and a control group of euthyroid neonates (range ¼ 34-700 mg/L). 63 In the neonates with congenital hypothyroidism, irrespective of cause, the range was ,2.0-1100 mg/L. A more recent study 64 found a range of serum Tg of ,1.0 -18.7 mg/L in athyreosis while those with an ectopic gland had a range of 4.5-123 mg/L.…”
Section: Other Indications For the Measurement Of Serum Tgmentioning
confidence: 99%